DEVELOPMENT OF AN INTRANASAL DUAL VACCINE AGAINST NOROVIRUS AND HEPATITIS B VIRUS FOR INDONESIAN POPULATION - Syari Intan, Novia
Hepatitis B virus (HBV) infection is a serious health problem in Indonesia. A therapeutic vaccine to treat chronic HBV infection and a prophylactic vaccine to prevent HBV transmission through sexual contact as one of the most frequent HBV transmission routes are needed. The combination of two HBV antigens, namely HBcAg and HBsAg, has been shown to be potential as an HBV therapeutic vaccine while HBsAg itself has been widely used as an HBV prophylactic vaccine. Mucosal and systemic immune responses need to be induced by this combination of vaccines so that the intranasal route of delivery was chosen. To increase the immunogenicity of the antigen, the P particle Norovirus (NoV) platform was used. Moreover, the use of P particle NoV also provides protection against NoV as a non-bacterial cause of gastroenteritis. Both HBV and NoV vaccines need to elicit a mucosal and systemic immune response so that they can be delivered together intranasally. The design of chimeric P particle Norovirus (NoV) GII.4-HBV as a dual intranasal vaccine candidate has been made in previous studies. To make a vaccine suitable for the Indonesian population, the dominant NoV genotype, GII.2, was used. While the inserted HBV parts are a known immunodominant epitopes, the NoV epitopes present in this design have not been identified. This study aims to predict the presence of epitopes in the P domain NoV in chimeric P particle NoV GII.2-HBV and its population coverage towards the HLA allele variation in Indonesian populations and to carry out expression and purification of chimeric P domain NoV GII.2-HBV protein as the first step in immunogenicity studies. Epitope prediction was carried out in silico using BepiPred 2.0, ABCpred (B cell) and NetMHCIIpan, NetCTLpan, and NetMHCpan (T cell) programs. The expression of chimeric P domain NoV GII.2-HBV was performed in this study using Escherichia coli with the T7 expression system while protein purification was carried out by Ni-NTA column and analyzed by SDS-PAGE. The results of in-silico analysis showed the presence of 2 strong candidates for B-cell epitopes that were conserved on the surface of the protein. 15 CD4+ T cell epitopes and 35 CD8+ T cell epitopes are predicted to provide 100% population coverage of the HLA allele variation of the Javanese-Sundanese population as the largest population in Indonesia. With this potential character, chimeric protein P domain NoV GII.2-HBV is then expressed and purified. The SDS-PAGE analysis results showed the success of expression and purification by obtaining a protein band with ~ 39.5 kDa in size. We concluded that the NoV B cell epitopes were conserved and predicted to be on the surface of chimeric P particle NoV GII.2-HBV, while the analysis of population coverage based on the NoV T cell epitopes provided good coverage for the Indonesian population, especially Javanese and Sundanese. Expression and purification of chimeric P domain NoV GII.2-HBV protein was successfully performed. In general, this vaccine design has good potential and its development needs to be studied further.